White gastric mucosa during endoscopy as a new endoscopic feature of chronic ischemic gastritis: A case report. Issue 1 (13th December 2022) - Ichita, Chikamasa; Sasaki, Akiko; Isogai, Naoko; Sumida, Chihiro; Nishino, Takashi; Kubota, Jun; Shionoya, Kento; Kimura, Karen
Abstract: Chronic ischemic gastritis (CIG) requires early diagnosis and treatment as complications of thromboembolism can be fatal. Although computed tomography (CT) is useful in the diagnosis of CIG, it is difficult to diagnose from a patient's history, endoscopic findings, and tissue biopsy. Identification of the key findings that motivate computed tomography is an important issue. We report a case of CIG diagnosed by endoscopic findings of white patches of mucosa over time. A 63‐year‐old man presented with epigastric pain. He had a history of repeated gastric ulcers of an undetermined cause. We performed upper endoscopy and observed the appearance of multiple white patches on the gastric mucosa. Central vessel stenosis was considered, and aortic computed tomography revealed complete occlusion of the superior mesenteric artery and stenosis of the celiac artery. We carried out a surgical bypass and found no postoperative endoscopic mucosal changes or abdominal pain. White patch changes in the gastric mucosa over time during endoscopy may indicate CIG. This finding may help in the future diagnosis of CIG.